Analisa Faktor-faktor yang Mempengaruhi Keputusan Nasabah Memilih Koperasi Syariah (Studi Kasus STEBI Tanggamus) - Agustomi Agustomi; Fauzi Fauzi (Dinar Islamic Review, 2021)
The purpose of this research is to analyze the factors that influence customer decisions (cultural, social, personal, and psychological) in choosing savings and loans and sharia financing (KSPSS). In this study, the place used for research is the Koperasi STEBI Tanggamus. In this study, the population used were the customers of the Koperasi STEBI Tanggamus. Sampling in this study using the convenience sampling method as many as 91 samples. The type of research used in this research is descriptive quantitative research. The technique of collecting with a questionnaire. The data analysis method used is descriptive statistical test, validity test, and reliability test. Hypothesis testing using multiple linear regression test, partial test (t test), simultaneous test (F test), and by using the coefficient of determination test. The results showed that partially cultural factors had a significant effect on customer decisions in choosing the Koperasi STEBI Tanggamus. Partially social factors, personal or personal factors, and psychological factors have no significant effect on customer decisions in choosing the Koperasi STEBI Tanggamus. Cultural, social, personal, and psychological factors simultaneously influence customer decisions in choosing the Koperasi STEBI Tanggamus.